In the book "understanding physics" by Mansfield, the author derives the constant acceleration equations and at the start he derives the equation $v=v_0+A(t-t_0)$. I immediately noticed that setting $t=0$ in this gives $v(0)=v_0-At_0$, ie the equation is equivalent to $v=v(0)+At$.

However, the author seems to get this by a more complicated method. He first says "It is often convenient to choose the origin and starting instant so that x=0 when t=0. In this case, $x_0=0$ and $t_0=0$, and the equation $v=v_0+A(t-t_0)$ becomes $v=v_0+At$."

The reason this is confusing me, is because the equation he gets is simply $v=v(0)+At$ (since he defines $v_0$ as the value of $v$ at $t_0$, but he just said that $t_0=0$, therefore his $v_0$ has now become $v(0)$ in the last equation).

Therefore, he essentially is saying: "It is often convenient to choose the origin and starting instant so that x=0 when t=0. In this case, $x_0=0$ and $t_0=0$, and the equation $v=v_0+A(t-t_0)$ becomes $v=v(0)+At$."

I am not sure if you see why this is confusing, but he seems to be saying that "in this case", ie in the case where $x_0=0$ when $t_0=0$, then $v=v(0)+At$. But this is not true, since it is not only true in this case, because I clearly showed above that his initial equation $v=v_0+A(t-t_0)$ already implies $v=v(0)+At$. So we do not need the special case of $x_0=0$ when $t_0=0$ for $v=v(0)+At$ to result from $v=v_0+A(t-t_0)$.

Therefore, I am not sure what the author meant by saying "in this case" and am wondering if I have gone wrong somewhere.


You are correct, but you miss one subtlety. His equation after the assumption of $t_0=0$ was $$ v = v_0 + At $$ While yours was $$ v = v(0) + At $$

You can probably see it now, but the distinction is that $v_0$ is not necessarily equal to $v(0)$. In fact $v_0$ is defined to be $v(t_0)$, so for a nonzero acceleration you can show that $v_0=v(0)$ only if $t_0=0$.

(On the other hand the assumption that $x_0=0$ is completely unnecessary)

  • $\begingroup$ I didn't say $v_0=v(0)$ in general, I said it is true based on the author's assumption to let $x_0=0$ and $t_0=0$. This is why I was confused, because he already had the equation from the start. $\endgroup$ – Raghib Jan 1 '18 at 17:10
  • $\begingroup$ Here is how I derived $v(0)$ equation: The author has $v=v_0+A(t-t_0)$, so letting $t=0$ we get $v(0)=v_0+A(-t_0)$, and substituting this back into the equation gives $v=v(0)+At$. I am not saying that $v_0=v(0)$, I am using the substitution $v(0)=v_0+A(-t_0)$. However, at the end it actually does become $v_0=v(0)$ since the author lets $t_0=0$. Please let me know if I am wrong. $\endgroup$ – Raghib Jan 1 '18 at 17:20

I too find the quoted paragraph puzzling.

If we consider $x$ and $v$ to be functions of $t,$ and say that $t_0$, $x_0,$ and $v_0$ are the "starting" time, position, and velocity, then $x_0 = x(t_0)$ and $v_0 = v(t_0).$ If we now set our coordinate system so that $x=0$ when $t=0$ (as the author writes), it is true that $x(0) = 0,$ but let's consider an example in which some particle moves according to $x_0 = -1,$ $t_0 = -1,$ $v_0 = 1,$ and $A = 0.$ In that example we will also have $x=0$ when $t=0.$ So I do not see how "$x=0$ when $t=0$" implies that $x_0 = 0$ or that $t_0 = 0.$

Here is a different version of the quote from the book, which I have modified so that I think it is correct:

It is often convenient to choose the starting instant so that $t_0=0$. Then the equation $v=v_0+A(t-t_0)$ becomes $v=v_0+At$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.